(3eNJUQ TQM CUhd GdWhais - (3YdGA GdOjf Ydj Hf eMeO Hf Ydj Hf YHO Gddg GdcfGfi GdYSbdGfis; (3GdUQUQj , SdjeGf Hf YHO Gdbhj Hf YHO GdcQje GdWhaj, fLe GdOjf CHh GdQHjY,J (B716 (3g` s ((3CMeO Hf EHQGgje Hf fUQ Gddg Hf CMeO GdcfGfi GdYSbdGfi s)
(3ChdgG (B:s
(3CeG HYO ajbhd GdabjQ Edi QMeI QHg s
(3BNQgG (B:s
(3adgPG CgedfG PcQg GNJUGQkG BNQ TQM eNJUQ GdTjN fLe GdOjf GdWhai GdYdGeI s
(3GdQhVI ai GdCUhd dGHf bOGeI GdebOSi cTa GdXfhf L(B2 (3U` (B924s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs